2017
DOI: 10.21273/hortsci11981-17
|View full text |Cite
|
Sign up to set email alerts
|

Flowering of the Cover Crop Sunn Hemp, Crotalaria juncea L.

Abstract: Sunn hemp, Crotalaria juncea L., is a warm-season legume that is planted before or after a vegetable cash crop to add nutrients and organic matter to the soil, for weed-growth prevention, and to suppress nematode populations. Sunn hemp flowers may also provide nectar and pollen for pollinators and enhance biological control by furnishing habitat for natural enemies. Despite these benefits, adoption in the United States has been limited because of restricted availability of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…It's surprising that larvae feeding on plants produced from seed purchased as 'Tropic Sun' from Hawaii were half as small, although the difference was not significant. Larval weights from feeding on ' AU Golden' and on PI 322377, the germplasm line used to create this cultivar (Cho et al 2016;Mosjidis 2014), were very similar to Tillage Sunn ™ , one of the other lines used in a Florida sunn hemp flowering study (Meagher et al 2017). The line from South Africa that was used in the field trials in this study produced small larvae with relatively high levels of mortality, similar to work conducted in Brazil (Dias et al 2016).…”
Section: Discussionsupporting
confidence: 58%
“…It's surprising that larvae feeding on plants produced from seed purchased as 'Tropic Sun' from Hawaii were half as small, although the difference was not significant. Larval weights from feeding on ' AU Golden' and on PI 322377, the germplasm line used to create this cultivar (Cho et al 2016;Mosjidis 2014), were very similar to Tillage Sunn ™ , one of the other lines used in a Florida sunn hemp flowering study (Meagher et al 2017). The line from South Africa that was used in the field trials in this study produced small larvae with relatively high levels of mortality, similar to work conducted in Brazil (Dias et al 2016).…”
Section: Discussionsupporting
confidence: 58%
“…Meagher et al. (2017) tested different sunn hemp cultivars in north‐central Florida (lat. 29 o N), AU Golden (photoperiod insensitive) and Tropic Sunn (photoperiod sensitive), and observed that Tropic Sunn produced a very limited number of flowers with no viable seedpods, whereas AU Golden had a substantial number of flowers and seed production.…”
Section: Discussionmentioning
confidence: 99%
“…Sunn hemp flowering is dictated by photoperiod sensitivity (Mosjidis & Wang, 2011), and Crescent Sunn and Blue Leaf may be dependent on short days to onset flower; however, the short days during the autunm in South Florida were not sufficent to trigger flowering in these two genotypes. Meagher et al (2017) tested different sunn hemp cultivars in north-central Florida (lat. 29 o N), AU Golden (photoperiod insensitive) and Tropic Sunn (photoperiod sensitive), and observed that Tropic Sunn produced a very limited number of flowers with no viable seedpods, whereas AU Golden had a substantial number of flowers and seed production.…”
Section: Discussionmentioning
confidence: 99%
“…We only documented 2 Xylocopa specimens with blue vane traps, although actively counting visiting bees in later studies with other varieties of sunn hemp resulted in finding large numbers of Xylocopa micans Lepeletier and Xylocopa virginica (both Hymenoptera: Apidae) (Meagher et al 2019). We believe that sunn hemp lines that successfully produce flowers earlier in the season can provide food and habitat for pollinators and beneficial insects (LeFéon et al 2013;Meagher et al 2017).…”
Section: Discussionmentioning
confidence: 93%
“…Bee bowl traps have been shown to catch smaller-bodied bees disproportionately relative to larger bees (Cane et al 2000;Roulston et al 2007), and may under-sample bee species richness when there are abundant floral resources nearby (Mayer 2005;Wilson et al 2008;Baum & Wallen 2011). We had hoped that sunn hemp would flower earlier in the season, but because of an error in ordering, a sunn hemp line that has short daylength flowering was used (Meagher et al 2017). Pollination of the large yellow papilionaceous flowers of Crotalaria (Fabaceae) species occurs when bees land on the flower keel and wing petals and force their tongues into the nectar well at the base of the standard petal (Le Roux & Van Wyk 2012).…”
Section: Discussionmentioning
confidence: 99%